Burden or benefit? Effects of providing education about and the option to request additional genomic findings from diagnostic exome sequencing: A randomized controlled trial. Issue 12 (December 2021) - Rini, Christine; Roche, Myra I.; Lin, Feng-Chang; Foreman, Ann Katherine M.; Khan, Cynthia M.; Griesemer, Ida; Waltz, Margaret; Lee, Kristy; O'Daniel, Julianne M.; Evans, James P.; Berg, Jonathan S.; Henderson, Gail E.
Highlights: Genomic sequencing can yield findings unrelated to primary sequencing indication. Education about them and the option to learn them may burden or benefit patients. Findings show a few benefits and no harms of providing this education and option. Findings may inform recommendations for returning a broad range of genomic findings. Abstract: Objective: Many people prefer to learn secondary or "additional" findings from genomic sequencing, including findings with limited medical actionability. Research has investigated preferences for and effects of learning such findings, but not psychosocial and behavioral effects of receiving education about them and the option to request them, which could be burdensome or beneficial (e.g., causing choice overload or satisfying strong preferences, respectively). Methods: 335 adults with suspected genetic disorders who had diagnostic exome sequencing in a research study and were randomized to receive either diagnostic findings only (DF; n = 171) or diagnostic findings plus education about additional genomic findings and the option to request them (DF + EAF; n = 164). Assessments occurred after enrollment (Time 1), after return of diagnostic results and—for DF + EAF—the education under investigation (Time 2), and three and six months later (Times 3, 4). Results: Time 2 test-related distress, test-related uncertainty, and generalized anxiety were lower in the DF + EAF group ( p s = 0.025–0.043). There were no other differences. Conclusions: Findings show limited benefits and no harms of providing education about and the option to learn additional findings with limited medical actionability. Practice implications: Findings can inform recommendations for returning additional findings from genomic sequencing (e.g., to research participants or after commercial testing).